2021
DOI: 10.1002/mma.7940
|View full text |Cite
|
Sign up to set email alerts
|

On the limit of a two‐phase flow problem in thin porous media domains of Brinkman type

Abstract: We study the process of two‐phase flow in thin porous media domains of Brinkman type. This is generally described by a model of coupled, mixed‐type differential equations of fluids' saturation and pressure. To reduce the model complexity, different approaches that utilize the thin geometry of the domain have been suggested. We focus on a reduced model that is formulated as a single nonlocal evolution equation of saturation. It is derived by applying standard asymptotic analysis to the dimensionless coupled mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Observe that (K P ) i3 = (K P ) 3,j = 0, i, j = 1, 2, 3, so that Ṽ can be rewritten to have (15) with K P given by (16).…”
Section: Darcy' Law For the Ptpmmentioning
confidence: 99%
See 1 more Smart Citation
“…Observe that (K P ) i3 = (K P ) 3,j = 0, i, j = 1, 2, 3, so that Ṽ can be rewritten to have (15) with K P given by (16).…”
Section: Darcy' Law For the Ptpmmentioning
confidence: 99%
“…To finish the introduction, we give a list of recent references concerning studies of partial differential equations in TPM. Studies related to Newtonian fluids through TPM can be found in Anguiano and Suárez-Grau [11,14], Armiti-Juber [16], Bayada and et al [17], Larsson et al [26], Suárez-Grau [31], Valizadeh and Rudman [32], Wagner et al [33] and Zhengan and Hongxing [36]. Concerning generalized Newtonian fluids see Anguiano and Suárez-Grau [7,12,15], for Bingham fluids see Anguiano and Bunoiu [8,9], for compressible and piezo-viscous flow see Pérez-Ràfols et al [27], and for micropolar fluids see Suárez-Grau [30] and for diffusion problems see Anguiano [5,6] and Bunoiu and Timofte [21].…”
Section: Introductionmentioning
confidence: 99%